Evidence supporting the use of recombinant activated factor VII in congenital bleeding disorders - Pär I Johansson; Sisse R Ostrowski (Dove Medical Press, 2010)
Pär I Johansson, Sisse R OstrowskiCapital Region Blood Bank, Section for Transfusion Medicine, Rigshospitalet, University of Copenhagen, Copenhagen, DenmarkBackground: Recombinant activated factor VII (rFVIIa, NovoSeven®) was introduced in 1996 for the treatment of hemophilic patients with antibodies against coagulation factor VIII or IX.Objective: To review the evidence supporting the use of rFVIIa for the treatment of patients with congenital bleeding disorders.Patients and methods: English-language databases were searched in September 2009 for reports of randomized controlled trials (RCTs) evaluating the ability of rFVIIa to restore hemostasis in patients with congenital bleeding disorders.Results: Eight RCTs involving 256 hemophilic patients with antibodies against coagulation factors, also known as inhibitors, were identified. The evidence supporting the use of rFVIIa in these patients was weak with regard to dose, clinical setting, mode of administration, efficacy, and adverse events, given the limited sample size of each RCT and the heterogeneity of the studies.Conclusion: The authors suggest that rFVIIa therapy in hemophilic patients with inhibitors should be based on the individual’s ability to generate thrombin and form a clot, and not on the patient’s weight alone. Therefore, assays for thrombin generation, such as whole-blood thromboelastography, have the potential to significantly improve the treatment of these patients.Keywords: hemophilia, inhibitors, coagulation factor VIII, coagulation factor IX, rFVIIa, NovoSeven, FEIBA, hemostasis, RCT